Making futures: equity and social justice in higher education timescapes. Issue 6 (17th August 2020) - Bunn, Matthew; Bennett, Anna
ABSTRACT: Neo-liberal higher education is preoccupied with the future, with study increasingly viewed as being important for and in the future, rather than valuable in the present. We argue that a preoccupation with the future itself has become the generator of the present as precarious. Paradoxically, the certainty of future transformation or change, forms present uncertainty, which is also experienced as distressing and frantic in pace. We must work to keep up with change and control our futures. We thus explore how these 'proleptic' schemas [Webb and Gulson 2012. "Policy Prolepsis in Education: Encounters, Becomings, and Phantasms." Discourse: Studies in the Cultural Politics of Education 33 (1): 87–99], where the future is represented as existing before it actually does, threatens equity and social justice in HE. Overly hasty responses risk overlooking the important differences in people's pasts, presents and futures. Being present, in order to get to know our students, what they know and want for their futures, in all their rich diversity, must be at the forefront of HE.